Toxicity study of erythroxylumcuneatum kurz, and its effects on rodent neurobehavioural properties - Shahril, Mohamad Syahmi (2015)
Therapeutic and new alternative potential compounds of natural product have been widely used in pharmaceutical industry. Interest on alternative efforts to search for new compounds with less or no adverse effects has led to the discovery of new potential plants in the treatment of diseases. Erythroxylum cuneatum, also known as „Chinta Mula‟ plant among Malaysians has been discovered and recently proven to possess antiwithdrawal properties with a potential to be explored as a source of new drugs for the treatment of addiction. Erythroxylum cuneatum can be found in primary and secondary forests. Due to less information on this plant, this elusive plant was investigated advancely to understand its roles and potential as a new source of pharmacologically in the pharmaceutical industry. Thus, further scientific exploration was made to understand the mechanisms of action involving toxicity and neurobehavioral properties were proposed. Three different extracts were produced from the leaves of Erythroxylum cuneatum which were aqueous, methanol and alkaloid extracts and three semi pure compounds were fractionized from the crude alkaloid extracts by different solvent systems. There is no toxicity profile on this plant, thus, their toxicity on cell lines, brine shrimp and mice were determined. In the cytotoxicity and Brine Shrimp Lethality Assay (BSLA) studies, alkaloid extract was found to be toxic to the cells and brine shrimp compared to the aqueous extract. Indeed, in the BSLA study, aqueous extract seems to give no toxic effect to the shrimp at the high dose as compared to the alkaloid extract. However, for the in-vivo toxicity study, aqueous extract showed almost similar toxic effect as alkaloid extract. The presence of alkaloid compounds that is typically associated with the central nervous system (CNS) has directed the study of behavioral profiles. Locomotor activity in Open-Field Test (OFT), anxiety study using elevated-plus maze (EPM) and working memory task using Novel Object Discrimination test (NOD) were performed for the determination of neurobehavioral profiles. Sixty four male Wistar rats were used in the study and divided into eight groups which were normal group, control group, three groups of positive drug control and three groups of three different doses of alkaloid extracts (5, 25 and 50 mg/kg). All doses were chronically administrated intraperitoneally to the test group for 21 consecutive days and evaluated on day 21 after the last dose. The findings showed that locomotor activity was not significantly increased (P>0.05) in all doses of alkaloid extracts. In anxiety study, two parameters were performed on each rat including time spent in open arms and open arm entries frequency. All doses did not increase in both parameters as compared to the standard drug Diazepam. In the Novel Object Discrimination test, alkaloid treated rats did not show any significant discrimination between the old and new object (P>0.05) thus, it can be interpreted as a memory deficit. After the completion of behavioral study, rats were sacrificed and their kidney and liver were collected to evaluate any morphological changes. Normal to mild changes were noted in both liver and kidney of treated rats with 5 and 25 mg/kg of alkaloid extract while the highest dose (50 mg/kg) did not show any morphological changes. From this data, it is clear that Erythroxylum cuneatum does not affect behavioral properties. In conclusion, Erythroxylum cuneatum could be a scientist new hope in the process of developing new anti withdrawal drugs as Erythroxylum cuneatum has a low toxic effects and does not produce any behavioural changes.